Critical care management of chimeric antigen receptor T‐cell therapy recipients. (6th October 2021) - Shimabukuro‐Vornhagen, Alexander; Böll, Boris; Schellongowski, Peter; Valade, Sandrine; Metaxa, Victoria; Azoulay, Elie; von Bergwelt‐Baildon, Michael
Abstract: Chimeric antigen receptor (CAR) T‐cell therapy is a promising immunotherapeutic treatment concept that is changing the treatment approach to hematologic malignancies. The development of CAR T‐cell therapy represents a prime example for the successful bench‐to‐bedside translation of advances in immunology and cellular therapy into clinical practice. The currently available CAR T‐cell products have shown high response rates and long‐term remissions in patients with relapsed/refractory acute lymphoblastic leukemia and relapsed/refractory lymphoma. However, CAR T‐cell therapy can induce severe life‐threatening toxicities such as cytokine release syndrome, neurotoxicity, or infection, which require rapid and aggressive medical treatment in the intensive care unit setting. In this review, the authors provide an overview of the state‐of‐the‐art in the clinical management of severe life‐threatening events in CAR T‐cell recipients. Furthermore, key challenges that have to be overcome to maximize the safety of CAR T cells are discussed. Abstract :